Prognostic Value of Tricuspid Annular Plane Systolic Excursion (TAPSE), Right Ventricular Fractional Area Changes (RV FAC) and Pulses Tissue Doppler S' Wave (PTD S') at 30 Days after Care of Acute Miocardial Infarction Patients in Haji Adam Malik Hospital - Ilhami, Fadli; Nasution, Ali Nafiah; Andra, Cut Aryfa (CoinReads Media Prima, 2023)
Introduction: Echocardiography is a reliable and simple method of hemodynamic monitoring that can be used on every IMA patient. Tricuspid Annular Plane Systolic Excursion (TAPSE), Right Ventricular Fractional Aera Changes (RV FAC), and Pulses Tissue Doppler S' Wave (PTD S') are the three main parameters of ventricular electrocardiography. The purpose of this study is to understand the reliability of the right ventricle function prognostic indicators TAPSE, PTD S', and RV FAC with regard to the MACE at 30 days following the occurrence of the AMI in RSUP H. Adam Malik Medan Method: This study is an ambispective observational analytic study with sampling carried out at one time (cross-sectional study) on 88 AMI patients at the HAM Hospital who were treated from March 2022 to June 2022 and performed echocardiography in the first 24 hours and measured TAPSE, PTD S' and RV FAC. And followed for 30 days to see the MACE in patients. Bivariate test was conducted to assess the correlation between variables. To determine which independent variables were more effective at predicting MACE, a multivariate logistic regression test was then run. The effectiveness of the independent factors in predicting MACE was also assessed using ROC analysis. Results: The total subjects were 88 AMI patients consisting of 39 (44.3%) patients who experienced MACE and 49 (55.6%) patients who didn’t. The prognostic values of TAPSE, PTDS' and RV FAC on MACE at 30 days were related by bivariate analysis with P Value 0.001 but only PTD S’ showed logistic regression results that were consistent with P Value < 0.001. Based on ROC analysis obtained by PTD S' can predict MACE with AUC = 0.894 Conclusion: Echocardiographic measurement PTD S’ has a good prognostic value to predict MACE within 30 days in AMI patients.